Experimental Validation of a 2-Bit Reconfigurable Unit-Cell for Transmitarrays at Ka-Band - Clemente, Antonio; Diaby, Fatimata; Palma, Luca Di; Dussopt, Laurent; Sauleau, Ronan (IEEE access, 2020)
This paper presents the experimental results of a 2-bit electronically reconfigurable unit-cell for transmitarrays at Ka-band. The proposed unit-cell architecture is based on a six-metal layers design and three dielectric substrates. Two patch antennas are printed respectively on the top and bottom layers of the stack-up to achieve an antenna-filter-antenna structure. To implement the desired 2-bit phase resolution, two p-i-n diodes are bonded on each patch. The unit-cell has been fabricated and characterized in a specific waveguide simulator. The measurement results are compared to the simulated ones and show minimum transmission loss in the range 1.5 - 2.3 dB. The 3-dB fractional bandwidth is in the range 10.1 - 12.1%.